Implementasi Protokol Keamanan Dan Segmentasi Jaringan Dalam Project Pembangunan WLAN Untuk PT Pan Pacific Insurance - Riyan Almakhi; Ade Surya Budiman; Rachmawati Darma Astuti (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2023)
Security of data and network devices is essential in the development of a computer network, either in the creation of new computer networks or in the development of existing computer networks. PT. Pan Pacific Insurance as a company that holds large amounts of data along with its supporting computer network's infrastructure, focuses on security aspects in addition to performance aspects in its computer network. To get the flexibility of its computer network, the company developed a wireless local area network (WLAN) in line with the relocation of its head office. The Existing company's network needs to be improved with a WLAN network, so it does not only improve employee performance and provides the best security for company data. For those purposes, the authors applied the use of Cisco Wireless LAN Controller (WLC), Cisco Access Point and applied the WPA+WPA2 PSK security protocol for the SSID used by employees. Using this protocol when employees want to connect to the network wireless, they will be forced to type the password that has been set. In addition to implementing the security protocol, the author also applies the Web Policy Authentication security protocol for the SSID used by guests. So that guests who want to connect to a wireless network will be directed to a web browser to be asked to enter a username and password first. A series of security protocols, also added with network segmentation on each SSID to use a different network address. Thus, the essence of network security and performance is expected to increase. From the results of the tests carried out, obtained security guarantees on the PT. Pan Pacific Insurance successfully directs every user connected to the network as part of the security protocol implemented. Furthermore, with network segmentation, user traffic is more controlled because guests get their network segmentation, so they don't interfere with network traffic for users or company staff in company operations.